2011
DOI: 10.1200/jco.2010.31.2231
|View full text |Cite
|
Sign up to set email alerts
|

Multifactorial Approach to Predicting Resistance to Anthracyclines

Abstract: Given its high NPV, the A-Score could become, if further validated, a useful clinical tool to identify those patients who do not benefit from anthracyclines and could therefore be spared the non-negligible adverse effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
115
0
6

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 172 publications
(121 citation statements)
references
References 28 publications
0
115
0
6
Order By: Relevance
“…pCR was defined as loss of the invasive component of the primary tumor in one study (33) and no residual invasive cancer in the breast and axillary lymph nodes in other seven studies (34)(35)(36)(37)(38).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…pCR was defined as loss of the invasive component of the primary tumor in one study (33) and no residual invasive cancer in the breast and axillary lymph nodes in other seven studies (34)(35)(36)(37)(38).…”
Section: Discussionmentioning
confidence: 99%
“…We further evaluated whether AR mRNA expression were associated with response to neoadjuvant CT (anthracyclines AE taxanes). Out of 1,005 patients from eight datasets (33)(34)(35)(36)(37)(38), 235 (23%) patients achieved pCR, 765 (76%) did not, while five samples were inadequate for the analysis. High AR expression levels showed significant association with lower pCR rate (OR, 0.57; 95% CI, 0.44-0.74, P < 0.001) in the univariate analysis while not significant in a multivariate model (OR, 0.74; 95% CI, 0.54-1.01, P ¼ 0.063; Fig.…”
Section: Prognostic Significance Of Ar Expressionmentioning
confidence: 99%
“…In order to investigate this, we used a collection of breast cancer studies where patients had received neo-adjuvant cytotoxic chemotherapy [26][27][28][29] and for whom data on pathological complete response (pCR) were available (N = 871). A tumor is said to have undergone pCR if, following surgery, no residual tumor cells remain upon pathological examination.…”
Section: Intclust Subtypes Show Large Differences In Chemosensitivitymentioning
confidence: 99%
“…The genes were chosen from literature review on the basis of their being identified as (i) possible prognostic factors in residual disease at protein (4,(6)(7)(8)(9)(10) or mRNA level (11), (ii) as significantly up-or downregulated, but of unknown prognostic value in residual disease (12)(13)(14)(15)(16)(17)(18)(19)(20), (iii) as predictive of chemotherapy resistance (6,11,16,19,(21)(22)(23)(24)(25)(26)(27)(28)(29), and/or (iv) identified as possible prognostic factors over several previous datasets (26,(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41). In addition to the previously established prognostic factors ESR1 and ERBB2, the genes were also chosen to represent different pathways and biological processes of known implication in tumor progression or response to therapy, such as stemcellness (ALDH1A1, CD44, and STAT3), proliferation (TOP2A, MKI67, and AURKA), apoptosis (BCL2, BCL2L1, and PAWR), immunologic response (CD3D, CXCL13, and STAT1), epithelial-to-mesenchymal transition (EMT; SNAI1, SNAI2, SOX9, and TWIST), stromal activation (DECORIN, ...…”
Section: Introductionmentioning
confidence: 99%